2016
DOI: 10.1097/md.0000000000005502
|View full text |Cite
|
Sign up to set email alerts
|

Hypervascularity is more frequent in medullary thyroid carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
2
13
0
3
Order By: Relevance
“… 29 31 Two studies that compared US features of papillary thyroid cancer (PTC) versus MTC both found larger lesion size, heterogeneous echotexture, and hypervascularity as significantly more characteristic of MTC than PTC. 30 , 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 31 Two studies that compared US features of papillary thyroid cancer (PTC) versus MTC both found larger lesion size, heterogeneous echotexture, and hypervascularity as significantly more characteristic of MTC than PTC. 30 , 31 …”
Section: Resultsmentioning
confidence: 99%
“…29 US features associated with MTC include irregular shape, height/width ratio <1, lack of a peripheral halo, hypoechogenecity, calcification (typically macrocalcification), and hypervascularity. [29][30][31] Two studies that compared US features of papillary thyroid cancer (PTC) versus MTC both found larger lesion size, heterogeneous echotexture, and hypervascularity as significantly more characteristic of MTC than PTC. 30,31 US classification systems can be applied for both diagnosis and prognosis in MTC.…”
Section: Imagingmentioning
confidence: 99%
“…In pathology, MTC histological slices show more or less angiogenesis. Lai et al [ 11 ] reported that hypervascularity is more frequent in MTC when compared with PTC. In this case within the neoplasmic stromal, angiopoiesis was present.…”
Section: Resultsmentioning
confidence: 99%
“…In the present series, 80.15% of PTMCs were deficient in vascularity. According to the study reported by Lai et al [25], 72.4% of MTCs showed hypervascularity, which might be induced by the rapid division and growth of MTCs cells, resulting in a faster rate of proliferation than PTCs. In this study, an abundant blood supply was also commonly detected in MTMCs (58.70%), but the proportion was not as high as that reported in the literature.…”
Section: Cystic Changes Are Not Common In Ptmcs Andmentioning
confidence: 96%